An Enantioselective Synthesis of Substituted Cyclohexanone Derivatives with an All‐Carbon Quaternary Stereocenter by Using an Organocatalytic Asymmetric Domino Double Michael Addition. Issue 23 (8th July 2015) - Chen, Chi‐Han; Ko, Chi‐Ting; Reddy, Ganapuram Madhusudhan; Lee, Chia‐Jui; Lin, Wenwei
Abstract: A cinchona alkaloid‐catalyzed enantioselective method has been developed for the synthesis of densely functionalized cyclohexanone derivatives with excellent diastereoselectivities and good enantioselectivities [diastereomeric ratio ( dr ) >95:5 and an enantiomeric excess ( ee ) value up to 86 %]. The products have an all‐carbon quaternary center that contains both a cyano and ester group flanked by two vicinal tertiary stereocenters. By using a one‐pot procedure, the tautomeric products were then transformed into the corresponding pyrazoles, which were obtained as single isomers in good yields. Abstract : A quinine‐catalyzed enantioselective method has been reported to generate polysubstituted cyclohexenes that have an all‐carbon quaternary center. The resulting isomeric product mixtures were easily converted into the corresponding pyrazoles through a one‐pot procedure.